2016
DOI: 10.1002/2016gl069473
|View full text |Cite
|
Sign up to set email alerts
|

Observations of whistler mode waves with nonlinear parallel electric fields near the dayside magnetic reconnection separatrix by the Magnetospheric Multiscale mission

Abstract: We show observations from the Magnetospheric Multiscale (MMS) mission of whistler mode waves in the Earth's low‐latitude boundary layer (LLBL) during a magnetic reconnection event. The waves propagated obliquely to the magnetic field toward the X line and were confined to the edge of a southward jet in the LLBL. Bipolar parallel electric fields interpreted as electrostatic solitary waves (ESW) are observed intermittently and appear to be in phase with the parallel component of the whistler oscillations. The po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
92
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(102 citation statements)
references
References 49 publications
(88 reference statements)
10
92
0
Order By: Relevance
“…There are instances of narrowband wave power between 1,000 and 2,000 Hz as MMS4 briefly passes out of the boundary layers and into the magnetosphere that tracks with f ce /2 (e.g., at 06:40:05–20 UT). This type of emission has been recently observed with MMS near reconnection sites by Le Contel et al () and Wilder et al () and indicates close proximity to the source region of this possible whistler mode‐type wave. There is also a clear band of wave power tracking with f lh at 06:39:15–25 UT.…”
Section: Encounters With the Llbl Separatrixmentioning
confidence: 97%
“…There are instances of narrowband wave power between 1,000 and 2,000 Hz as MMS4 briefly passes out of the boundary layers and into the magnetosphere that tracks with f ce /2 (e.g., at 06:40:05–20 UT). This type of emission has been recently observed with MMS near reconnection sites by Le Contel et al () and Wilder et al () and indicates close proximity to the source region of this possible whistler mode‐type wave. There is also a clear band of wave power tracking with f lh at 06:39:15–25 UT.…”
Section: Encounters With the Llbl Separatrixmentioning
confidence: 97%
“…For instance, Deng and Matsumoto [2001] reported a good mediation of reconnection rate by whistlers at the Earth's magnetopause, using the Geotail data; Wei et al [2007] observed whistlers prior to reconnection and enhancement of whistlers during reconnection in the Earth's magnetotail, using the Cluster data; Huang et al [2016] presented two types of whistlers during Hall magnetic reconnection, using the Cluster data; Graham et al [2016], Le Contel et al [2016a], and Wilder et al [2016] observed strong whistler emissions in the separatrix region, using the Magnetospheric Multiscale (MMS) data; Khotyaintsev et al [2016] reported whistlers in the outflow region, using MMS data. For instance, Deng and Matsumoto [2001] reported a good mediation of reconnection rate by whistlers at the Earth's magnetopause, using the Geotail data; Wei et al [2007] observed whistlers prior to reconnection and enhancement of whistlers during reconnection in the Earth's magnetotail, using the Cluster data; Huang et al [2016] presented two types of whistlers during Hall magnetic reconnection, using the Cluster data; Graham et al [2016], Le Contel et al [2016a], and Wilder et al [2016] observed strong whistler emissions in the separatrix region, using the Magnetospheric Multiscale (MMS) data; Khotyaintsev et al [2016] reported whistlers in the outflow region, using MMS data.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we exclude unstructured whistler mode hiss [Thorne et al, 1973;Bortnik et al, 2009;Li et al, 2012] and other types of whistler mode emission known to be generated at different locations in the magnetosphere, like at high latitudes on the dayside on compressed auroral field lines [Stenberg et al, 2005;Vaivads et al, 2007], or in the magnetotail in connection with dipolarization fronts Deng et al, 2010;Breuillard et al, 2016], or in the separatrix regions of magnetic reconnection sites at the dayside magnetopause [Øieroset et al, 2014;Graham et al, 2016;Le Contel et al, 2016;Wilder et al, 2016]. Thus, we exclude unstructured whistler mode hiss [Thorne et al, 1973;Bortnik et al, 2009;Li et al, 2012] and other types of whistler mode emission known to be generated at different locations in the magnetosphere, like at high latitudes on the dayside on compressed auroral field lines [Stenberg et al, 2005;Vaivads et al, 2007], or in the magnetotail in connection with dipolarization fronts Deng et al, 2010;Breuillard et al, 2016], or in the separatrix regions of magnetic reconnection sites at the dayside magnetopause [Øieroset et al, 2014;Graham et al, 2016;Le Contel et al, 2016;Wilder et al, 2016].…”
Section: Introductionmentioning
confidence: 99%